Pengaruh Struktur Modal, Ukuran Perusahaan, dan Pertumbuhan Perusahaan terhadap Profitabilitas dan Dampaknya terhadap Nilai Perusahaan - Riyana, Nita; Kusumawardhani, Ratih; Rinofah, Risal (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to examine the influence of capital structure, firm size, and firm growth on profitability and its impact on firm value. The population used in this research is all Food and Beverage Companies listed on the Indonesia Stock Exchange during the 2018-2022 period, totaling 84 companies. The sampling technique used was purposive sampling technique by considering several criteria and a sample of 16 companies was obtained with an observation period of 5 years. This research uses multiple linear regression analysis techniques and path analysis with the help of SPSS version 26 analysis tools. The research results show that capital structure has a negative and significant effect on profitability. Firm size has a positive and significant effect on profitability. Firm growth has a positive and insignificant effect on profitability. Meanwhile, profitability has a positive and significant effect on firm value. The influence of capital structure on profitability both directly and indirectly is 13,2%. The influence of firm size on profitability both directly and indirectly is 2,4%. The influence of firm growth on profitability both directly and indirectly is 3,6%. The total or combined influence of the capital structure, firm size, and firm growth variables on profitability is 19,2%, while the remaining 80,8% is influenced by other variables not included in this research. The influence of profitability on firm value is 25,9%, while the remaining 74,1% is influenced by other variables not included in this research.